Analysis of groundwater–lake interaction by distributed temperature sensing in Badain Jaran Desert, Northwest China. Issue 9 (21st November 2015) - Liu, Chuankun; Liu, Jie; Wang, Xu‐Sheng; Zheng, Chunmiao
Abstract: The Badain Jaran Desert is the second largest desert of China with a total area of 49 200 km 2 . At least 72 perennial lakes are scattered throughout the desert, sustaining a unique desert–lake ecosystem. Groundwater of various origins was believed to play an essential role in maintaining those desert lakes, but hydrological measurements are lacking due to difficult field conditions. This study applied the distributed temperature sensing technique to continuously measure temperature variations in one of the desert lakes – the Badain Lake – to identify groundwater discharge to the lake based on the temperature differences between groundwater and lake water. Because temperature may be influenced by various unforeseen and temporary factors, it is critical to discern those factors that may affect the temperature such as solar radiation and vertical temperature stratification and to ensure that the temperature variations of the lake water as detected by the distributed temperature sensing are mainly caused by groundwater discharge. A time window was identified during which the groundwater discharge is the dominant factor that determines the temperature pattern of the lake water. The results show that the temperature near the eastern and southeastern lakeshore of the eastern Badain Lake is colder than the average, indicating that this area is the main groundwater discharge zone. Near the northwestern lakeshore adjacent to a sand dune, a weak cold abnormal area was identified, indicating that the sand dune is another recharge source to the lake through channelling the local precipitation toward the lake. The contribution from the sand dune, however, appeared to be less than that from the regional groundwater flow. This study provides the first identification of the temperature abnormal areas, which imply groundwater discharges into desert lakes and contributes to a better understanding of the unique desert–lake ecosystem. Copyright © 2015 John Wiley & Sons, Ltd.